Frequency of Uterine Rupture in Multigravida Women With Different BMI - Seema, .; Akhtar, Zubaida; Akber, Lubna; Musa, .; Khan, Sajjad Ullah (Biological and Clinical Sciences Research Journal, 2025)
Uterine rupture remains a life-threatening obstetric complication, particularly among multigravida women. Maternal nutritional status, as reflected by body mass index, may influence the risk, yet local evidence remains limited. Objective: To determine the frequency of uterine rupture in multigravida women with different BMI groups presenting at Khyber Teaching Hospital, Peshawar. Methods: Eighty multigravida women aged 18 to 40 years with singleton pregnancies>36 weeks’ gestation were included in this study. Body mass index was calculated for every patient and was categorized as underweight, normal weight, and overweight/obese. Data was analysed using SPSS 26. Uterine rupture was assessed in all patients and across BMI groups using the chi-square test, with a P-value set at ≤0.05. Results: The cohort had a mean age of 29.29 ± 6.43 years, a mean gestational age of 39.18 ± 1.49 weeks, a mean parity of 3.38 ± 1.15, and a mean BMI of 24.15 ± 4.44 kg/m2. The overall frequency of uterine rupture was 33.8%. The majority of rupture cases (18, 66.7%) occurred in the overweight/obese groups, followed by 7 (25.9%) in the normal weight group and 2 (7.4%) in the underweight group. Higher parity (>3) (P = 0.006), lower economic background (P = 0.004), and rural residence (P = 0.02) were significantly associated with uterine rupture. Conclusion: The frequency of uterine rupture in multigravida women was considerably higher in the overweight/obese BMI category than in the underweight and overweight categories.